Obsessive-Compulsive Disorder in Five Selected Poems - Amelia Insaniyah (sarasvati, 2025)
This study, entitled Obsessive-compulsive Disorder in Five Selected Poems discusses individuals with obsessive-compulsive disorder (OCD), a mental illness marked by intrusive thoughts, urges, or sensations (obsessions) that drive the individuals' repeated actions or behaviours (compulsions), as depicted in five selected poems. The purpose of this study is to examine how the characteristics of OCD are depicted in the five selected poems and to assess how these issues influence the patterns in writing the poems. The objects of this study are five poems: O.C.D., and Static Electricity by Neil Hilborn; You Can Take Off Your Sweater, I’ve Made Today Warm by Paige Lewis; and I’m Not Crazy, and I Can...I Will...Replace Those Weeds with Beautiful Flowers! by Cherry Pedrick. The theory used is psychoanalytical theory, as proposed by Sigmund Freud (2005). This study employs a descriptive qualitative method, involving a line-by-line analysis within each stanza. The findings reveal that obsessive-compulsive disorder significantly affects the writing patterns in these poems. This influence lends uniqueness to the literary works, offering individuals affected by OCD a space to freely express and share their inner selves through poetry.